2021
DOI: 10.11648/j.ajim.20210902.14
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Vitamin D in Patients Attending at Tertiary Care Hospital, Bangladesh

Abstract: Introduction: Vitamin D deficiency is a common condition prevalent among both developed and developing countries where it is seen mostly in females. It has been linked to various skeletal and non-skeletal diseases. This study was done to find out the distribution of Vitamin D deficiency attending the outpatient department of a tertiary care hospital. Methods: This descriptive cross-sectional study was done among the patients attending the outpatient department of a tertiary care hospital in Dhaka, Bangladesh. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…Globally, the female gender is one of the most important predictors of vitamin D deficiency 13,14 . The increased frequency seen in females was comparable with other studies in Saudi Arabia (78.1%) 10 , Libya (58.8%) 14 , Nepal (76.1%) 11 , and Bangladesh (46%) 17 . This finding was due to some factors that females predominate for vitamin D deficiency.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Globally, the female gender is one of the most important predictors of vitamin D deficiency 13,14 . The increased frequency seen in females was comparable with other studies in Saudi Arabia (78.1%) 10 , Libya (58.8%) 14 , Nepal (76.1%) 11 , and Bangladesh (46%) 17 . This finding was due to some factors that females predominate for vitamin D deficiency.…”
Section: Discussionsupporting
confidence: 89%
“…The observation of various reports of older people or increased ages that have lowered vitamin D serum concentration is because the older group might not be having vitamin D and calcium supplements or decreased dietary intake, diminished sunlight exposure, reduced skin thickness, impaired intestinal absorption, and impaired hydroxylation of vitamin D in liver and kidney [15][16][17] . Another necessary explanation is that those younger ages in this study have higher vitamin D levels than older ages where the MENA region (the Middle East/Africa) generally spends more time outdoors compared with other age groups with lower vitamin D levels 13,14,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Bhattarai et al in their study found 34.8% deficient, 35.9% insufficient, 28.7% normal and 0.6% hypervitaminosis D (Bhattarai et al, 2019). Sadiya et al had also conducted similar study in Bangladesh and found 14.1% deficient, 34.7% insufficient and 51.2% normal level of vitamin D (Sadiya et al, 2021). In a study conducted by Lee et al in 2008 found the prevalence of vitamin D deficiency as approximately 30-50% of the general population which was close to that of our study as 57.7% (Lee et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
“…Vitamin D is one of the fat-soluble prohormones which has essential roles in the maintenance of various physiological processes (Sadiya et al, 2021). Maintenance of calcium and phosphate homeostasis is played by the essential role of vitamin D and these both minerals have important role for proper bone health (Renkema et al, 2008).…”
Section: Introductionmentioning
confidence: 99%